Factors predicting difficult laparoscopic cholecystectomy: a single institution experience - Bunkar, Shiv K.; Yadav, Sushil; Singh, Amit; Agarwal, Kalpana; Sharma, Preeti; Sharma, Amar C. (International Surgery Journal, 2017)
Background: Laparoscopic cholecystectomy is one of the most common operations performed by general surgeon. This study was performed to evaluate pre-operative factors predicting difficult laparoscopic cholecystectomy. Methods: A prospective study was carried out at Jawaharlal Nehru Medical College Hospital, Ajmer, a tertiary care centre in Middle East Rajasthan, India. In present study we included 100 patients diagnosed with symptomatic gallstones disease on the basis of history, clinical examinations and USG findings and underwent laparoscopic cholecystectomy in our hospital by a single surgeon during the period of July 2014 to July 2016. These all patients were evaluated for a group of risk factors and preoperatively these risk factors were given a score between 0-5 labeled as easy, 5-10 as difficult and 11-15 as very difficult. Statistical analysis was done by Fischer’s test and chi square test. Results: BMI >30, previous medical disease like DM, palpable gall bladder, prior hospitalization pericholecystic collection and impacted stone are significant risk factors to predict difficult laparoscopic cholecystectomy. Conclusions: The studied scoring system had a positive prediction value for easy prediction of 94% and for difficult prediction of 100%.